Pleural subxyphoid drain confers better pulmonary function and clinical outcomes in chronic obstructive pulmonary disease after off-pump coronary artery bypass grafting: a randomized controlled trial - Guizilini,Solange (2014)
Objective: To evaluate the lung function and clinical outcome in severe chronic obstructive pulmonary disease in patients undergoing off-pump coronary artery bypass grafting with left internal thoracic artery graft, comparing the pleural drain insertion in the intercostal versus subxyphoid region. Methods: A randomized controlled trial. Chronic obstructive pulmonary disease patients were randomized into two groups according pleural drain site: II group (n=27) - pleural drain in intercostal space; SI group (n=29) - pleural drain in the subxyphoid region. Spirometry values (Forced Vital Capacity - and Forced expiratory volume in 1 second) were obtained on preoperative and 1, 3 and 5 postoperative days. Chest x-ray from preoperative until postoperative day 5 (POD5) was performed for monitoring respiratory events, such as atelectasis and pleural effusion. Pulmonary shunt fraction and pain score was evaluate preoperatively and on postoperative day 1. Results: In both groups there was a significant decrease of the spirometry values (Forced Vital Capacity and Forced expiratory volume in 1 second) until POD5 (P<0.05). However, when compared, SI group presented less decrease in these parameters (P<0.05). Pulmonary shunt fraction was significantly lower in SI group (P<0.05). Respiratory events, pain score, orotracheal intubation time and postoperative length of hospital stay were lower in the SI group (P<0.05). Conclusion: Subxyphoid pleural drainage in severe Chronic obstructive pulmonary disease patients determined better preservation and recovery of pulmonary capacity and volumes with lower pulmonary shunt fraction and better clinical outcomes on early postoperative off-pump coronary artery bypass grafting.